2015
DOI: 10.3892/mco.2015.588
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the smaller target volume for stage III non-small cell lung cancer treated with intensity-modulated radiotherapy

Abstract: Abstract. The present study reports the local recurrence, distant metastasis, progression-free survival, overall survival and radiation toxicity between two arms of stage III non-small cell lung cancer (NSCLC) treated with intensity-modulated radiotherapy (IMRT); one arm with clinical target volume (CTV) and the other without CTV. The two arms of local recurrence, distant metastasis, progression-free survival, overall survival, grade 3-4 radiation esophagitis and hematological toxicity had no statistical signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…The second reason can be deduced from the present status of treatment failure patterns for LA-NSCLC treated with concurrent chemoradiotherapy. Consistent with many previous studies (22)(23)(24), we found that major failure occurred in the distant areas, which may shadow over the local-regional recurrences; most local-regional recurrences occurred with IN-PTV-g rather than subclinical regions, implying that the current standard radiation dose for LA-NSCLC (60 Gy per 30 fractions) may be insufficient in eliminating gross tumors. Thus, in such a state, using radical radiation doses to treat the invisible subclinical lesions even when the visible gross tumors cannot be well controlled is excessive.…”
Section: Discussionsupporting
confidence: 89%
“…The second reason can be deduced from the present status of treatment failure patterns for LA-NSCLC treated with concurrent chemoradiotherapy. Consistent with many previous studies (22)(23)(24), we found that major failure occurred in the distant areas, which may shadow over the local-regional recurrences; most local-regional recurrences occurred with IN-PTV-g rather than subclinical regions, implying that the current standard radiation dose for LA-NSCLC (60 Gy per 30 fractions) may be insufficient in eliminating gross tumors. Thus, in such a state, using radical radiation doses to treat the invisible subclinical lesions even when the visible gross tumors cannot be well controlled is excessive.…”
Section: Discussionsupporting
confidence: 89%
“…Decades of experience led to the conclusion that 45-50 Gy results in high control rates for subclinical disease in patients with epithelial tumors (3)(4)(5)(6). However, recent studies have shown that omission of the CTV in lung cancer radiotherapy does not compromise local tumor control (7,8). This latter result may reflect sufficient dose coverage to the subclinical disease extent within certain margins by delivering volumes in which at least 60 Gy were administered for gross tumor eradication.…”
Section: Introductionmentioning
confidence: 99%
“…In their retrospective series of 105 patients, Liang et al . found that omission of a 6–8mm CTV margin resulted in smaller PTVs, similar rates of local recurrence, and decreased grade 3–4 radiation pneumonitis (7). Because 4DCT simulation was not used, ITV margins ranged from 3–15mm.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies evaluated the effect of target volume margins on clinical outcomes for inoperable NSCLC (79). We hypothesized that smaller margins would not compromise locoregional control and would associate with fewer acute toxicities in the setting of concurrent CRT with PET/CT-based treatment planning, 4DCT simulation, and daily CBCT.…”
Section: Introductionmentioning
confidence: 99%